The mechanism underlying streptozotocin injection for the development of a nontransgenic Alzheimer’s disease animal model - Titisari, Nurina; Ahmad, Hafandi; Samsulrizal, Nurdiana; Fauzi, Ahmad; Abdul Razak, Intan Shameha (Faculty of Veterinary Medicine, University of Tripoli, 2025)
Streptozotocin (STZ) is a widely used chemical agent in biomedical research. It is primarily known for its ability to induce high blood glucose levels in animal models by selectively destroying pancreatic beta cells. Nonetheless, many studies have also used STZ to generate animal models of diabetic complications, such as Alzheimer’s disease (AD) animal models. STZ induction promotes hyperglycemia, which activates numerous mechanism pathways that result in the production of pathogenic AD characteristics, including beta-amyloid accumulation and neurofibrillary tangles. Numerous theories exist to elucidate the mechanisms underlying diabetes and AD; however, studies on the potential of an animal model of STZ-induced AD remain limited. Thus, this review summarizes the pathogenesis associated with STZ exposure, particularly in AD animal model studies related to diabetes. More specifically, this study will discuss the relationship between increased blood glucose levels after STZ injection and the process of beta-amyloid formation and insulin dysfunction in the brain.